COMPOSITE ARMATURES IN CONSTRUCTION PROSPECTS FOR APPLICATION (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article presents the advantages and disadvantages of using composite reinforcement in construction in comparison with traditional steel reinforcement.